(untitled) (Stato, Chiese e pluralismo confessionale, 2013)
Contributo sottoposto a valutazione SOMMARIO: 1. La “novità” dell’ordinanza del Tribunale di Lecce 8 ottobre 2012 – 2. Il precedente belga – 3. Uno sguardo sulla dottrina civilistica del respondeat superior nell’esperienza americana – 4. La fattispecie esaminata dai giudici salentini e la questione della soggettività della Curia arcivescovile – 5. (segue) Il riconoscimento della responsabilità indiretta ex art. 2049 c.c. – 6. Le ragioni della non configurabilità di una posizione di responsabilità del vescovo ex art. 2049 c.c. - Appendice. It’s “Déjà vu” in Case Law: Vicarious Liability of the Diocesan Bishopfor the Intentional Torts committed by his Priests ABSTRACT: This Article addresses the issue of a Diocesan Curia’s liability for the intentional torts (sexual assault) committed by his parish priest. The paper takes as a starting point a recent Italian ruling that found a master-servant relationship between the Diocesan Curia and parish priest. The Court also held that a parish priest who committed a intentional tort (sexual assault), causally connected to the relationship, is acting within the scope of employment, so that the Diocesan Curia is vicariously liable. The Author suggests a comparative approach to the guidelines of Belgian and American case law on the subject of sexual abuse committed by clergy and examines the legal aspects of the topic as they are ruled by Italian law, which should lead to reject the conclusion of imputing a vicarious liability upon the Diocesan Curia. KEYWORDS: Vicarious liability of churches for sexual misconduct; Respondeat superior liability; Master-servant relationship in the religious organizations.